1999
DOI: 10.1002/(sici)1097-0215(19990129)80:3<413::aid-ijc13>3.0.co;2-i
|View full text |Cite
|
Sign up to set email alerts
|

Schedule-dependent interaction of doxorubicin, paclitaxel and gemcitabine in human breast cancer cell lines

Abstract: We showed previously that a sequential treatment with doxorubicin (4 hr) followed by paclitaxel (24 hr) (Dox→Pacl) induces a synergistic cytotoxic effect in the BRC‐230 breast cancer cell line and in human primary breast cancer cultures. The validity of this experimental finding was confirmed in a clinical phase I/II study on advanced breast cancer patients. To improve the cytotoxic effect obtained by the Dox→Pacl sequence, we analyzed the effect of adding gemcitabine (Gem) to the Dox→Pacl sequence in a precli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

6
39
0

Year Published

2002
2002
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(46 citation statements)
references
References 14 publications
6
39
0
Order By: Relevance
“…This is of special relevance about tumor cells with WT p53 (e.g., when gemcitabine application follows the administration of a drug that blocks cell cycle progression). Indeed, gemcitabine efficacy was decreased when administered immediately after a doxorubicin-paclitaxel combination but re-established when pretreated cells were first allowed to enter S phase (15). Thus, especially when treating tumors with a WT p53 status using drug combinations, premature cell cycle arrest should be avoided to ensure the efficacy of nucleoside analogues.…”
Section: Discussionsupporting
confidence: 53%
“…This is of special relevance about tumor cells with WT p53 (e.g., when gemcitabine application follows the administration of a drug that blocks cell cycle progression). Indeed, gemcitabine efficacy was decreased when administered immediately after a doxorubicin-paclitaxel combination but re-established when pretreated cells were first allowed to enter S phase (15). Thus, especially when treating tumors with a WT p53 status using drug combinations, premature cell cycle arrest should be avoided to ensure the efficacy of nucleoside analogues.…”
Section: Discussionsupporting
confidence: 53%
“…Based on in vitro data suggesting a potential synergistic interaction between the two drugs (Zoli et al, 1999;Chow et al, 2000), specific tests in preclinical models are ongoing in our laboratories in order to analyse the antitumour activity of the GEM/PLD combination and possibly clarify the underlying mechanisms of drug interaction.…”
Section: Discussionsupporting
confidence: 93%
“…The use of drug combinations, which are considered a gold standard in the first-line approach (Berek et al, 1999;Ozols, 2000), is usually discouraged in the recurrent setting because of higher toxicity, and the lack of any evidence of benefit in terms of survival (Sabbatini et al, 1998;Colombo et al, 1999); nevertheless, the better toxicity profile expressed by some new categories of drugs allows the hypothesis that the rationalised choice of drugs with different mechanisms of action and toxicity patterns might increase the chances of response and favourably affect the clinical outcome. In this context, the combination of two of the above-mentioned drugs, namely GEM and PLD seemed particularly intriguing for several reasons: (i) both the drugs have shown activity in ovarian cancer Gordon et al, 2000Gordon et al, , 2001Markman, 2002); (ii) their different mechanisms of action are likely to hamper a cross resistance; (iii) the combination of GEM and doxorubicin has been reported to result in synergistic antiproliferative activity in vitro (Zoli et al, 1999;Chow et al, 2000); (iv) finally, the nonoverlapping toxicity profiles of GEM and PLD warrant the analysis of their combination in the clinical setting.…”
mentioning
confidence: 99%
“…Recent studies have shown the importance of modulating the cell cycle to exploit the effect of drug combinations (8,22). In the present study, flow cytometry demonstrated that both pemetrexed and gemcitabine caused an accumulation of cells in S phase, as a result of the inhibition of DNA synthesis.…”
Section: Discussionmentioning
confidence: 99%